Footwear-related variability in running. (2nd January 2016) - Schrödter, Erik; Brüggemann, Gert-Peter; Hamill, Joseph; Rohr, Eric; Willwacher, Steffen
Abstract : The manner of adapting one's running biomechanics when wearing different footwear designs appears to be individual-specific. Applying the preferred movement path theorem, wearing less than optimal running shoes bears the risk of forcing the joints to leave their preferred path and load unadapted joint areas that might be overused during sport activities. The goal of this article is to introduce a method quantifying a person's biomechanical responsiveness towards footwear, the so-called 'footwear-related variability', and to explore corresponding determinants. Eighty-nine participants were tested wearing six different running shoe conditions. They performed isometric strength tests for knee and ankle extensor muscles. Further, anthropometrics, as well as lower extremity kinematics and kinetics during linear running at 3.5 m/s were recorded. Their stance phase normalized waveform patterns of running biomechanical data were analysed by means of the 'adjusted coefficient of multiple determination', quantifying how much footwear-induced biomechanical response occurred. The results showed that knee joint-specific footwear-related variability was higher in female participants than in male participants. Strength-generating capacity correlated with some footwear-related variability measures and men were found to be stronger than women. Footwear-related variability appeared to be influenced by the extent of knee adduction, hip inward rotation and ankle outward rotation moment, which are characteristic to distinguish between men's and women's running styles. Anatomical and anthropometric differences between men and women as well as strength capacity disadvantages might make women more susceptible to footwear-induced running biomechanical alterations. Future studies should investigate the relationship between footwear-related variability and overuse injuries, in order to find critical thresholds of footwear-related variability and identify groups of runners that need to be specifically targeted with injury preventing measures.